Fold stability during endolysosomal acidification is a key factor for allergenicity and immunogenicity of the major birch pollen allergen - Machado, Yoan; Freier, Regina; Scheiblhofer, Sandra; Thalhamer, Theresa; Mayr, Melissa; Briza, Peter; Grutsch, Sarina; Ahammer, Linda; Fuchs, Julian E.; Wallnoefer, Hannes G.; Isakovic, Almedina; Kohlbauer, Vera; et al. (Journal of allergy and clinical immunology, 2016)
The search for intrinsic factors, which account for a protein's capability to act as an allergen, is ongoing. Fold stability has been identified as a molecular feature that affects processing and presentation, thereby influencing an antigen's immunologic properties. We assessed how changes in fold stability modulate the immunogenicity and sensitization capacity of the major birch pollen allergen Bet v 1. By exploiting an exhaustive virtual mutation screening, we generated mutants of the prototype allergen Bet v 1 with enhanced thermal and chemical stability and rigidity. Structural changes were analyzed by means of x-ray crystallography, nuclear magnetic resonance, and molecular dynamics simulations. Stability was monitored by using differential scanning calorimetry, circular dichroism, and Fourier transform infrared spectroscopy. Endolysosomal degradation was simulated in vitro by using the microsomal fraction of JAWS II cells, followed by liquid chromatography coupled to mass spectrometry. Immunologic properties were characterized in vitro by using a human T-cell line specific for the immunodominant epitope of Bet v 1 and in vivo in an adjuvant-free BALB/c mouse model. Fold stabilization of Bet v 1 was pH dependent and resulted in resistance to endosomal degradation at a pH of 5 or greater, affecting presentation of the immunodominant T-cell epitope in vitro. These properties translated in vivo into a strong allergy-promoting TH2-type immune response. Efficient TH2 cell activation required both an increased stability at the pH of the early endosome and efficient degradation at lower pH in the late endosomal/lysosomal compartment. Our data indicate that differential pH-dependent fold stability along endosomal maturation is an essential protein-inherent determinant of allergenicity.